2015
DOI: 10.1080/13803395.2015.1039963
|View full text |Cite
|
Sign up to set email alerts
|

Staying on the job: The relationship between work performance and cognition in individuals diagnosed with multiple sclerosis

Abstract: People with multiple sclerosis (MS) are apt to become unemployed as the disease progresses, and most research implies that this is due to diminishing mobility. Some studies have shown that presence of cognitive impairment also predicts employment status. Yet, no studies have examined how neuropsychological factors predict vocational performance among individuals with MS who remain employed. We assessed employer- and self-rated work performance, mobility status, and neuropsychological function in a sample of 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
0
12
0
2
Order By: Relevance
“…In a cohort of 337 individuals with the relapsing-remitting form of MS, 14 % of patients reported having to take time away from work due to their MS (absenteeism) and 47 % reported lost productivity at work as a result of their MS (presenteeism) [ 30 ]. Recently, several studies in small cohorts of patients with MS have suggested that fatigue, cognitive function and motor function may mediate the impact of disability on work status [ 31 33 ]. Our results confirm and extend these previous findings and highlight the relevance of increased disability as a driver of decrements in the capacity to work among patients with MS.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 337 individuals with the relapsing-remitting form of MS, 14 % of patients reported having to take time away from work due to their MS (absenteeism) and 47 % reported lost productivity at work as a result of their MS (presenteeism) [ 30 ]. Recently, several studies in small cohorts of patients with MS have suggested that fatigue, cognitive function and motor function may mediate the impact of disability on work status [ 31 33 ]. Our results confirm and extend these previous findings and highlight the relevance of increased disability as a driver of decrements in the capacity to work among patients with MS.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive symptoms can be one of the earliest symptoms and are present in up to 70% of patients [5, 6]. In fact, cognitive impairments in particular as well as depression, fatigue, and motor function resulting from MS have been shown to contribute to lowered work performance [7] and increased unemployment rates [811], reduced social activities [12], long-term disability [10], mental health [13], and overall quality of life [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as many as 65% of patients manifest significant cognitive impairment (Chiaravalloti & DeLuca, 2008; Rao, Leo, Bernardin, & Unverzagt, 1991a), and these deficits correspond with degraded activities of daily living (Basso, Shields, Lowery, Ghormley, Combs, Arnett, & Johnson, 2008; Chiaravalloti, DeLuca, Moore, & Ricker, 2005; Rao, Leo, Ellington, Nauertz, Bernardin, & Unverzagt, 1991b). For instance, neuropsychological dysfunction correlates with increased unemployment, diminished work performance, reduced psychosocial function, compromised ability to provide informed consent to medical treatment, and degraded management of daily domestic activities (Basso, Candilis, Johnson, Ghormley, Combs, & Ward, 2010; Baughman, Basso, Sinclair, Combs, & Roper, 2015; Rao et al, 1991b). …”
mentioning
confidence: 99%